Can digital literacy promote farmers’ cultivated land quality protection behaviors? - Shuang Hu; Huogen Wang (PLoS ONE, 2025)
Cultivated land is the most valuable agricultural resource and the most important factor of production. The protection of cultivated land quality is not only the foundation of national food security but also a strategic issue related to the sustainable development of the economy and society as a whole. This paper uses survey data from Jiangxi Province’s “Double Hundred and Thousand” in 2023 and empirically analyzes the impact of digital literacy on farmers’ cultivated land quality protection behaviors and its mechanism by using the O-probit model and the mediating effect model. The results show that digital literacy can effectively promote farmers’ cultivated land quality protection behaviors. Furthermore, digital literacy can indirectly promote farmers’ cultivated land quality protection behaviors through cultivated land protection cognition and digital use ability. Heterogeneity analysis indicates that farmers are more inclined to participate in cultivated quality protection behaviors In the context of better soil fertility conditions and higher digital literacy. Therefore, it is necessary to continuously improve the digital literacy of farmers, improve their awareness of cultivated land protection, and continuously strengthen their digital use ability.